Carbon Nanotube Based Metal–Organic Framework Hybrids From Fundamentals Toward Applications (Small 4/2022). Issue 4 (27th January 2022) - Chronopoulos, Demetrios D.; Saini, Haneesh; Tantis, Iosif; Zbořil, Radek; Jayaramulu, Kolleboyina; Otyepka, Michal
Abstract : Hybrid Materials In article number 2104628, Demetrios D. Chronopoulos, Kolleboyina Jayaramulu, Michal Otyepka, and co‐workers review the integration of carbon nanotubes with metal–organic frameworks into hybrid materials with augmented properties, otherwise difficult to accomplish by a single class of materials. The authors map the growth, structure, synthetic strategies, properties, and specific applications including water purification, gas storage and separation, sensing, electrocatalysis, supercapacitors, and batteries.